Perancangan Aplikasi Pencarian Makna Motif Batik Menggunakan Metode Galil Seiferas - Lisa Wardani (JURIKOM (Jurnal Riset Komputer), 2020)
For some people batik is only a cloth that is a characteristic of Indonesia, especially the area of Java, but not everyone knows that every motif on batik cloth has its own philosophical meaning where each meaning is closely related to human life. As the people of Indonesia it helps us to know the meaning behind the beauty of batik motifs, but not everyone knows the name of batik motifs and can search for meaning on the internet or what we often call browsing. The solution that can be done is to create an Android-based batik meaning search system that can provide convenience in searching for the meaning of batik motifs. Search is designed in an application that helps word search using string matching, the Galil Seiferas search algorithm. With the implementation of Seiferas Galil Algorithm on the Android-based batik meaning search system, it is expected to be able to carry out the right search process in displaying the meaning of batik motifs as well as being easier and faster. The system built is also very practical because it is based on Android, so it can make it easier for users to access anywhere